Analisis Kerusakan Diafragma Suling Pada Lokomotif Menggunakan Metode Fishbone Diagram - Ajeng Tyas Damayanti; Muhardono Muhardono; Tiara Septaningrum Subagio (Jurnal Syntax Admiration, 2024)
The analysis of the flute diaphragm damage in the locomotive was carried out using the Fishbone Diagram method to identify and group the main cause of the damage. This method visualizes the various factors that contribute to the problem through fishbone diagrams, allowing for an in-depth understanding of the relationship between causative factors such as design, materials, operational processes, and maintenance. The results of the analysis show that the damage to the distilled diaphragm is affected by a combination of internal and external factors, including material wear, excessive operational load, and lack of regular maintenance. These findings provide a basis for formulating more effective repair and prevention strategies, thereby improving the reliability and longevity of components in locomotives.